Game load dynamics in basketball: influence of playing position and match progression - Feu, Sebastián; García-Ceberino, Juan Manuel; López-Sierra, Pablo; Ibáñez, Sergio José (Frontiers in Physiology, 2026)
ObjectivesThis study explored the variability of internal and external load in professional basketball as a function of playing position and match quarter.MethodsFourteen ACB League players were monitored across three official games using ultra-wideband tracking and inertial measurement units (113 observations). Linear mixed-effects models assessed the influence of match progression and positional roles on kinematic, neuromuscular, and physiological load variables.ResultsExternal load indicators, specifically total distance covered (p < 0.001; ηp2 = 0.172), neuromuscular load (p < 0.001; ηp2 = 0.178), and high-intensity actions (p = 0.038; ηp2 = 0.030), declined progressively from the first to later quarters, confirming that the opening quarter imposes the highest physical demands. Guards performed more high-intensity actions per minute than centers (p = 0.045; ηp2 = 0.473). High inter-individual variability across several variables further supported the need for individualized monitoring.ConclusionsThese findings emphasize the importance of considering both match progression and positional roles when designing training programs. Understanding how load fluctuates across quarters could help coaches optimize periodization, adjust substitution strategies, and develop conditioning plans that had better reflect the repeated high-intensity efforts required in professional basketball.